2016
DOI: 10.1117/1.nph.3.4.045008
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal hemodynamic mapping by functional near-infrared spectroscopy in response to thermal stimulations over three body sites

Abstract: , "Prefrontal hemodynamic mapping by functional near-infrared spectroscopy in response to thermal stimulations over three body sites," Neurophoton. 3(4), 045008 (2016), doi: 10.1117/1.NPh.3.4.045008. Abstract. Functional near-infrared spectroscopy (fNIRS) was used to examine hemodynamic responses in the prefrontal cortex (PFC) during noxious thermal pain, induced by thermal stimulations over three different body sites over the right forearm, right temporomandibular joint, and left forearm. Functional NIRS meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…General linear model (GLM) analysis was used to quantify time-dependent ΔHbO patterns elicited during the handgrip task, by using a series of consecutive stimulation-specific boxcar functions convolved with a hemodynamic response function as a regressor, as in prior studies. [26][27][28] Only ΔHbO values were analyzed and reported in this study, because ΔHbR values were found to have similar and opposite qualitative trends but with smaller amplitudes and lower signal-to-noise ratio, as previously reported in other studies for other motor activation tasks and as seen in Fig. 1(c).…”
Section: Methodssupporting
confidence: 60%
“…General linear model (GLM) analysis was used to quantify time-dependent ΔHbO patterns elicited during the handgrip task, by using a series of consecutive stimulation-specific boxcar functions convolved with a hemodynamic response function as a regressor, as in prior studies. [26][27][28] Only ΔHbO values were analyzed and reported in this study, because ΔHbR values were found to have similar and opposite qualitative trends but with smaller amplitudes and lower signal-to-noise ratio, as previously reported in other studies for other motor activation tasks and as seen in Fig. 1(c).…”
Section: Methodssupporting
confidence: 60%
“…In this section, we focus on the HbO concentration changes to electrical stimuli. HbO response has often been observed to have a much higher SNR relative to HbR (Obrig et al, 2000 ; Yennu et al, 2016 ). In this study, an initial quality assurance analysis showed that the recorded HbO signals were more reliable in revealing the true shape of the hemodynamic response to external stimuli (results not shown).…”
Section: Resultsmentioning
confidence: 99%
“…7 Several difficulties remain regarding using the defined feature of the aPFC response (viz., the amplitude of HbO decrease) to detect pain in individual cases including: (1) the hemodynamic response to pain seems to show habituation with repetitive painful stimuli, leading to an insignificant difference in the response amplitude between innocuous stimuli and repeated noxious stimuli; 6,7 (2) distinct patterns in the shape of the hemodynamic response function (HRF) to pain (in terms of e.g., activations or deactivations, the peak/nadir time, dispersion, and undershoot time) have also been observed across different subjects, brain regions, and types of pain. In addition to the deactivations, multiple studies using fNIRS also reported pain-induced activations in the aPFC, largely in the lateral portion; [16][17][18][19] and (3) while the aPFC hemodynamic changes associated with pain were shown to be bilateral in some studies, others observed predominantly left-lateralized responses. 9,10 These results suggest using personalized analysis in the detection of the brain response to pain to properly characterize the signal.…”
Section: Introductionmentioning
confidence: 99%